Pierre Vilar(1906-2003) una obra de historiador - Luna, Pablo F. (2005)
Some of the characteristics of the practice of the office of historian by Pierre Vilar appear, just like their main contributions to the enrichment of the historical discipline. thinking historically, whereas vital and constant challenge, because in his opinión each citizen could and had practice it, avoinding the repetition of the committed errors discarding the negligences and tragedies of the past. Although needing the differences that separated to him of their present axponets, Pierre Vilar registered its work in the apirit of the founderds of the Annales magazines. But is work had two essential fidelities: on the one hand, the economic and social history of Ernest Labrousse, to that considered like its teacher. On the other hand the fecundity and vitality of the Maxist historical theary to understand the past and to try know the present.